A systemic lupus erythematosus patient presenting as type B insulin resistance complicated with cryoglobulinemia. (January 2017) - Huang, Q; Yan, Y; Zhao, H; Zuo, L
Systemic lupus erythematosus (SLE) patients may present with various symptoms and multisystem damage. We reported a 63-year-old male patient with SLE presenting as type B insulin resistance (TBIR) complicated with cryoglobulinemia. TBIR is an extremely rare disease, which is a manifestation of anti-insulin receptor antibodies (AIRA). Clinical feature is a sudden onset of hyperglycemia with major weight loss; however, the ensuing refractory hypoglycemia is more fatal. The average dosage of exogenous insulin is 5100 U/d. SLE patients with AIRA had poor prognosis, most of whom died of SLE activity. Cryoglobulins are immunoglobulins that reversibly precipitate in the cold, which will induce clinical symptoms. Non-infectious mixed cryoglobulinemia is frequently secondary to autoimmune diseases, such as SLE. Our patient was prescribed methylprednisolone (MP) and cyclophosphamide (CTX). Finally he had remission during the short-term follow-up. To our knowledge, this is the first case report of an SLE patient presenting as TBIR complicated with cryoglobulinemia.